Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Polly Getz dressed as a Las Vegas dancer and Mark Snauffer "The Magician" wearing black cape In background: Dave Maybary on saxophone, Nano Talanoa and Bob Fishman on guitar, Hal Bolen